Penggunaan Saringan Sebagai Alat Untuk Membantu Mengurangi Kadar Merkuri Yang Tercemar Di Desa Debowae Kecamatan Waelata Kabupaten Buru Provinsi Maluku - Alfiansa Umasugi; Erwin. B. Pattykayhattu; M. Said Karyani; Amin Jakfar (Journal Mechanical Engineering, 2023)
Gold mining activities on Buru Island legally or illegally cause water at several coordinate points to be contaminated with heavy metal types of mercury (Hg). Knowing the level of mercury in water is important to determine whether or not water can be consumed. This study aims to determine the level of mercury spread and how to overcome environmental damage due to mercury in water using eucalyptus charcoal. The method used in this study is quantitative by collecting data by observation, interviews, and literature studies. The variable in the study was filtering as a tool to reduce polluted mercury levels. The results of this study were carried out at 3 coordinates and 2 of the 3 coordinates showed a decrease in mercury levels, namely in the coodninat of the father's house, sub-district and village hall successively decreased by 18 μg / L and 2 μg / L. From the results it can be concluded that the level of mercury levels does not exceed the Quality standard figures placed according to the Ministry of Environment and Forestry No.Kep 51 of 2004 and eucalyptus charcoal can reduce mercury levels deposited in water. Based on the results of the research conducted, it turns out that there are still many shortcomings using this method. For future researchers who want to conduct similar research, in order to complement by answering the shortcomings of this study. Keywords: mercury, eucalyptus, filter